Apples and oranges: PTSD patients and healthy individuals are not comparable in their subjective and physiological responding to emotion induction and bilateral stimulation - Pape, Valeska; Sammer, Gebhard; Hanewald, Bernd; Schäflein, Eva; Rauschenbach, Fritz; Stingl, Markus (Frontiers in Psychology, 2024)
Objectives Bilateral stimulation is a core element of Eye Movement Desensitization and Reprocessing Therapy, a psychotherapeutic intervention for the treatment of Posttraumatic Stress Disorder (PTSD). Promising previous findings showed measurable physiological effects of bilateral stimulation in healthy individuals, but studies that replicated these findings in PTSD patients are sparse. Methods 23 patients with PTSD and 30 healthy controls were confronted with affective standard scripts (pleasant, neutral, unpleasant) while bilateral tactile stimulation was applied. Monolateral and no stimulation served as control conditions. Noise-induced startle reflex response (valence measure) and galvanic skin response (arousal measure) were used for physiological responses and the valence and arousal scale of the Self-Assessment-Manikin for subjective responses. Results Both groups showed a subjective distress reduction for unpleasant scripts and a subjective attention increase for positive scripts under bilateral stimulation. In healthy individuals, this was also for physiological measures, and a general startle-reducing effect of bilateral stimulation in the absence of affective stimuli was found. In PTSD patients, however, the effects were restricted on the subjective level, and no concomitant physiological effects were observed. Conclusions and significance The findings indicate, that generalizing the effects of BLS in healthy individuals to PTSD patients may be problematic. The herein-reported group differences can be explained by PTSD-specific peculiarities in emotion processing and cognitive processing style.